Mouse gastrulation: Attributes of transcription factor regulatory network for epiblast patterning. (18th October 2018) - Cui, Guizhong; Suo, Shengbao; Wang, Ran; Qian, Yun; Han, Jing‐Dong J.; Peng, Guangdun; Tam, Patrick P. L.; Jing, Naihe
Abstract : Gastrulation is a key milestone in early mouse development when multipotent epiblast cells are allocated to progenitors of diverse tissue lineages that constitute the ensemble of building blocks of the body plan. The analysis of gene function revealed that the activity of transcription factors is likely to be the fundamental driving force underpinning the lineage specification and tissue patterning in the primary germ layers. The developmental‐spatial transcriptome of the gastrulating embryo revealed the concerted and interactive activity of the gene regulatory network anchored by development‐related transcription factors. The findings of the network structure offer novel insights into the regionalization of tissue fates and enable tracking of the progression of epiblast patterning, leading to the construction of molecularly annotated fate maps of epiblast during gastrulation. Abstract : Analysis of the developmental‐spatial transcriptome of the gastrulating embryo revealed that the concerted and interactive activity of the regulatory networks of development‐related transcription factors offers insights into the regionalization of tissue fates and enables tracking of the developmental trajectory of cell populations, leading to the construction of molecular fate maps of epiblast during gastrulation.